De ruggengraat van het laagland. De boezem als schakel in de cultuurhistorische samenhang van het veengebied (Bulletin KNOB, 2017)
Given that the polder boezem* system, and in particular its network structure, is crucial to the spatial identity of the Dutch cultural landscape, a thorough cultural- historical understanding of that system is a precondition for the effective implementation of necessary future changes to the system. The boezem system in the western part of the Netherlands evolved over a period of more than five hundred years and exhibits considerable local differences in structure and form. It developed in response to a combination of a falling ground level and a rising sea level, which meant that excess water could no longer be drained without additional measures. Existing streams, watercourses and canals were accordingly diked in, modified and connected to one another to store water from the neighbouring polders or discharge it into the water outside the dikes. Within this system, a water level was established somewhere between the water levels inside and outside the dikes. To bridge the difference, sluices and pumping stations were built at discharge points. In order to fully understand the boezem system in the Randstad** study area, several different landscape layers were investigated. To determine the landscapearchitectural character, drawings were made based on historical maps and reconstructions, such as paleogeographic maps. The drawings were made using the overlay technique, which entails the superimposition of information from different historical sources. Each final drawing represents a reduction of information about the topic under consideration. This approach revealed three distinct landscape layers: the natural, the cultural-technical and the urban. The natural landscape layer is a reflection of geological formation: the landscape as shaped by the forces of nature. The cultural-technical landscape layer arose out of the confrontation between the natural landscape and the land reclamation grid. The urban landscape layer represents a further modification and transformation of the two previous layers. In the Randstad study area, boezems were created in a variety of landscape types: the coastal zone, the river landscape, the fenland areas and the marine clay landscape with polders. Each type of landscape has its own peculiarities, differences and similarities when it comes to the form of the storage basin (boezem). This shows that the boezem is not just an important link in the water management system; it is also an important spatial carrier of the various landscapes. Once identified and defined, those qualities can play a role in the preservation of the identity of the ever-changing landscape. The research method outlined in this article can be applied to a variety of water systems and can be of use in a revaluation of culturally and historically significant water systems worldwide.Translator’s note:* a boezem is a dike-enclosed storage basin created to manage excess water in the water network** the Randstad is a conurbation in the west of the Netherlands, flanked by the cities of Amsterdam, The Hague, Rotterdam and Utrecht